A Quranic Framework for the Integrated Economy of Hajj - Maram, Ahmad Nabilul; Anam, Aazliansyah Farizil; Maulana, Viqie Ixbal (Universitas Muhammadiyah Surakarta, 2025)
While the Hajj pilgrimage has significant economic dimensions, these are often underexamined from a theological perspective. This study aims to delineate the economic benefits of the Hajj as an integral component of its divine design. Adopting a qualitative, library-based methodology, this research performs a thematic analysis of the exegesis (tafsīr) of key Quranic passages, primarily from Surah Āli 'Imrān, Surah Al-Baqarah, and Surah Al-Hajj, to construct a holistic economic framework. The findings reveal a consistent Quranic theme that integrates economic activity into the pilgrimage. This is presented in a three-phase model: (1) Pre-Hajj economic mobilization, divinely catalyzed by the principle of financial capability (istiṭā'ah); (2) During-Hajj commerce, explicitly sanctioned as seeking